Among Multiple Needle Core Biopsy Samples, the One with the Highest Tumor Proportion Score Best Represents the PD-L1 Status of the Whole Surgical Specimen in Non–Small Cell Lung Cancer. Issue 3 (March 2022) - Sun, Wei; Yang, Xin; Wang, Haiyue; Wu, Jianghua; Chen, Mailin; Liu, Changling; Hu, Di; Huang, Xiaozheng; Jia, Ling; Kang, Qiang; Wu, Qi; Diao, Xinting; et al.
Abstract : The heterogeneity of programmed death-ligand 1 (PD-L1) status between core needle biopsies (CNBs) from one tumor has not been well studied before. The current study attempts to find out the best index using multiple core biopsies from one tumor which can better reflect the actual PD-L1 status. Random CNB was performed in surgical specimens from 170 consecutive non–small cell lung cancer samples. Fifty-one cases (41 cases with PD-L1 positive and 10 cases with PD-L1 negative) and 216 matched CNBs were analyzed by DAKO 22C3 PharmDx Link 48 Autostainer. The PD-L1 status was compared between the surgical specimens and matched CNBs. Heterogeneity of PD-L1 status between CNBs from one tumor was observed in 56% of PD-L1 positive cases. Different tumor proportion score (TPS) statistical forms with regard to the highest, mean, median, weighted average TPS, as well as TPS showed by the longest biopsy specimen and the biopsy with most tumor volume were compared. At a cut-off of 1%, the concordance rates were 94.1%, 88.2%, 90.2%, 86.3%, 86.3%, and 86.3%; At a cut-off of 50%, the concordance rates were 92.2%, 86.3%, 84.3%, 82.4%, 82.4%, and 86.3%, respectively. The CNB with the highest TPS can best represent PD-L1 status estimated by whole surgical specimen. The highest TPS among the multiple biopsies is a robust evaluation of the PD-L1 status, but not mean TPS, at the 1% and 50% cut-offs.